(3Odjd GdeUWdMGJ GdJfehjIs - (3eSYhO(B, (3eLjOs ((3OeTbs (3OGQ GdeOis, 2001)
(3eUWdMGJ Ydi GdUYjO GdJfehj Gdcdj hGdJNWjW dg,eUWdMGJ Ydi GdUYjO GdbWGYj hfhY GdfTGW,eUWdMGJ Ydi GdUYjO GdOjehZQGaj hGdGLJeGYj hGdGOGQj,eUWdMGJ Ydi GdUYjO GdeMGSHj Gdbhej hGdeGdj,eUWdMGJ Ydi UYjO GdeTQhY,eUWdMGJ GSdGejI aj GdGbJUGO,eUWdMGJ Ydi UYjO GdefXeGJ GdYQHjI hGdGbdjejI hGdOhdjIs
Keywords: (3GdeUWdMGJ GdJfehjIs